2001
DOI: 10.1099/00221287-147-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Competition among three predominant ruminal cellulolytic bacteria in the absence or presence of non-cellulolytic bacteria

Abstract: Competition among three species of ruminal cellulolytic bacteria -Fibrobacter succinogenes S85, Ruminococcus flavefaciens FD-1 and Ruminococcus albus 7 -was studied in the presence or absence of the non-cellulolytic ruminal bacteria Selenomonas ruminantium or Streptococcus bovis. Co-cultures were grown under either batch or continuous conditions and populations were estimated using species-specific oligonucleotide probes to 16S rRNA. The three cellulolytic species co-existed in cellobiose batch co-culture, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 24 publications
5
75
0
1
Order By: Relevance
“…R. albus was shown to be far more abundant than either R. flavefaciens and F. succinogenes in the bovine rumen whatever diet the animals were fed (Weimer et al, 1999). In vitro studies confirmed that R. albus outcompeted the two other species and became predominant in cultures where the three species were grown in the presence of cellulose as a growth substrate, alone or associated with non-cellulolytic species (Chen & Weimer, 2001). These studies tend to show that R. albus, R. flavefaciens and F. succinogenes do not act synergistically, but rather compete for their substrate, and that R. albus displays several ecological advantages that allow it to compete successfully.…”
Section: Ruminococcus Albus Ruminococcus Flavefaciens Andsupporting
confidence: 53%
“…R. albus was shown to be far more abundant than either R. flavefaciens and F. succinogenes in the bovine rumen whatever diet the animals were fed (Weimer et al, 1999). In vitro studies confirmed that R. albus outcompeted the two other species and became predominant in cultures where the three species were grown in the presence of cellulose as a growth substrate, alone or associated with non-cellulolytic species (Chen & Weimer, 2001). These studies tend to show that R. albus, R. flavefaciens and F. succinogenes do not act synergistically, but rather compete for their substrate, and that R. albus displays several ecological advantages that allow it to compete successfully.…”
Section: Ruminococcus Albus Ruminococcus Flavefaciens Andsupporting
confidence: 53%
“…While cellulolytic species may compete directly for cellulose (104,192,193,499,616), both cellulolytic and noncellulolytic species can compete for cellodextrin products of cellulose hydrolysis, in cross-feeding of nutrients, and in production of inhibitory compounds. A number of examples of such interactions have been demonstrated in defined mixed cultures (Table 2).…”
Section: Ecological Aspects Of Cellulose-degrading Communitiesmentioning
confidence: 99%
“…However, we detected two homologues of inh1 in unfinished genomic sequences of R. albus strain 8. inh1 and its two homologues are predicted to encode very similar proteins exhibiting more than 70% sequence identity and comprising a single N-terminal MMBL domain fused to a C-terminal region having an unknown function. Bacteriocins produced by ruminococcal bacteria are said to be part of the survival strategy of ruminal bacteria conferring competitive fitness in the ruminal environment (9). Inh1 and most other MMBL domain proteins of bacterial origin carry a potential N-terminal signal sequence that may direct these proteins to the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%